Transforming Islamic and Character Education: Enhancing Active Participation via Independent Curriculum in the Digital Era - Pitra Ariya Oktama; Ruswanto Ruswanto; Ais Isti’ana (ETDC: Indonesian Journal of Research and Educational Review, 2026)
In the digital era, student engagement in Islamic Religious Education (PAI) learning often faces obstacles, such as a lack of interest in conventional methods, a digital literacy gap, and a lack of confidence in actively participating in class. This study aims to analyze the implementation of the Independent Curriculum in increasing student active participation in Islamic Religious Education (PAI) and Character-Building subjects at Vocational School 4 Bandar Lampung, specifically by utilizing the potential of digital technology. This study used a qualitative approach with a descriptive design. The research subjects included Islamic Religious Education teachers and grade XI DKV 2 students. Data collection techniques were carried out through participant observation, in-depth interviews, and documentation studies to obtain a comprehensive picture of classroom learning dynamics. The research findings showed that the integration of digital media such as learning videos, interactive online quizzes, and digital discussion platforms significantly increased student engagement. Project-based learning methods, such as creating digital posters and Islamic preaching videos, proved effective in motivating students to be more active. However, the main challenges identified were variations in digital literacy levels and psychological barriers in the form of shyness that some students still experience when interacting in digital and physical spaces. This research provides practical insights for educators and educational institutions in optimizing the Independent Curriculum. Furthermore, the findings emphasize the importance of inclusive teaching strategies and improving digital literacy to create a learning environment that supports creativity and active student participation in the digital age.